(3GdOQ GdfVjO aj COH GdeajO hGdeSJajOs - (3HOQ GdOjf GdZRj , eMeO Hf eMeO Hf eMeO GdYGeQj GdZRj, HOQ GdOjf CHh GdHQcGJ,J (B984 (3g` s ((3Ydi Hf Ydi GdLGQM s)
(3ChdgG (B:s
(3GdMeO ddg fMeOg hfSJYjfg hHYO agPg QSGdI eNJUQI hLeYJgG ai aVjdI GdGTJZGd HGdYde hCOGHg GdHGH GdChd ai aVjdI GdETJZGd HGdYde hJYdeg s
(3BNQgG (B:s
(3Yf Ydi Hf CHj WGdH QVi Gddg Yfg Efg bGd ef CMH Cf jcJGd HGdceGd GdGhai ef GdCLQ jhe GdbjeI ajcf BNQ cdGeg ef eLdSg SHMGf QHc QH GdYRI YeG jUahf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf BNQ edJjSQ s
(3GdeNWhW edNU ef ebOeI TQM GdegPH ddTjN GdEeGe eMi GdOjf Gdfhhis
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B270s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs